A new very faint X-ray transient in the Galactic center. Issue Volume 9:Issue S303(2013) (22nd May 2014) - Soldi, Simona; Clavel, Maïca; Goldwurm, Andrea; Ponti, Gabriele; Terrier, Régis; Trap, Guillaume; Greiner, Jochen; Prinz, Tobias; Rau, Arne; Servillat, Mathieu
Abstract: A new X-ray transient, XMMU J174505.3-291445, has been detected within the 2012 XMM-Newton scan of the Galactic center. The short 4.7 ks flare, the highly absorbed X-ray spectrum and the relatively low luminosity of the event suggest the association of the source with either the class of very faint X-ray transients or that of supergiant fast X-ray transients. Further analysis, together with the identification of the possible infrared counterpart will help to unveil the true nature of XMMU J174505.3-291445.